2010
DOI: 10.1021/am900652h
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Pentacene Crystal Growth on Dielectric Roughness for Fabrication of Flexible Field-Effect Transistors

Abstract: The dependence of pentacene nanostructures on gate dielectric surfaces were investigated for flexible organic field-effect transistor (OFET) applications. Two bilayer types of polymer/aluminum oxide (Al(2)O(3)) gate dielectrics were fabricated on commercial Al foils laminated onto a polymer back plate. Some Al foils were directly used as gate electrodes, and others were smoothly polished by an electrolytic etching. These Al surfaces were then anodized and coated with poly(alpha-methyl styrene) (PAMS). For PAMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…Figure S5a,b (Supporting Information) shows the AFM images of 50 nm thick pentacene films obtained on the WG 3 NSs and the WG 3 film, respectively. The AFM measurements indicate that the lower mobility of the WG 3 NSs device was caused by the smaller pentacene grains grown on the relatively rough WG 3 NSs than that grown on smooth WG 3 film . Moreover, it is worth noting that the ON/OFF current ratio of the WG 3 NSs device was two orders of magnitude higher than that of the WG 3 film device, which is favorable to obtain a stable and reliable memory device.…”
mentioning
confidence: 91%
“…Figure S5a,b (Supporting Information) shows the AFM images of 50 nm thick pentacene films obtained on the WG 3 NSs and the WG 3 film, respectively. The AFM measurements indicate that the lower mobility of the WG 3 NSs device was caused by the smaller pentacene grains grown on the relatively rough WG 3 NSs than that grown on smooth WG 3 film . Moreover, it is worth noting that the ON/OFF current ratio of the WG 3 NSs device was two orders of magnitude higher than that of the WG 3 film device, which is favorable to obtain a stable and reliable memory device.…”
mentioning
confidence: 91%
“…As shown in Figure e, we can only observe the (00 l ′) diffraction peak, attributed to the “thin‐film phase,” with an interlayer spacing of 15.4 Å . This reveals that pentacene crystallizes with a herringbone arrangement and forms a fiber structure with the a–b plane oriented parallel to the substrate . The AFM images and XRD spectra indicate that the pentacene films were deposited with a polycrystalline structure due to the improved roughness of the CNF films by the spin‐coated PMMA layers.…”
Section: Resultsmentioning
confidence: 93%
“…Among various TMO‐based materials, MoO 3 was chosen as a hole‐injection barrier between IZO and pentacene, because organic devices with a MoO 3 buffer layer showed a good optical transparency in the visible light region and improved electrical characteristics . The pentacene active layer, which exhibits a high carrier mobility because of its crystal structure and the considerable overlap of the frontier molecular orbitals, was deposited using thermal evaporation. In the bottom‐gate/top‐contact structure, for high performance, the crystalline quality of pentacene is largely determined by the roughness of the dielectric layer.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that phase separation affects the exciton dissociation and the electron trapping ability of the doped electret layers. [27] Furthermore, X-ray diffraction (XRD) (shown in Figure S14, Supporting Information) and grazing-incidence X-ray diffraction (GIXD) (Figure 2) are employed to study the crystalline morphology of the TP layers. 25 nm of TP semiconductor layer was then deposited onto the electret layers by thermal evaporation.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%